Silver Nanoparticles-Decorated Titanium Oxynitride Nanotube Arrays for Enhanced Solar Fuel Generation - Khaled A. Soliman (Nature Portfolio, 2017)
Abstract We demonstrate, for the first time, the synthesis of highly ordered titanium oxynitride nanotube arrays sensitized with Ag nanoparticles (Ag/TiON) as an attractive class of materials for visible-light-driven water splitting. The nanostructure topology of TiO2, TiON and Ag/TiON was investigated using FESEM and TEM. The X-ray photoelectron spectroscopy (XPS) and the energy dispersive X-ray spectroscopy (EDS) analyses confirm the formation of the oxynitride structure. Upon their use to split water photoelectrochemically under AM 1.5 G illumination (100 mW/cm2, 0.1 M KOH), the titanium oxynitride nanotube array films showed significant increase in the photocurrent (6 mA/cm2) compared to the TiO2 nanotubes counterpart (0.15 mA/cm2). Moreover, decorating the TiON nanotubes with Ag nanoparticles (13 ± 2 nm in size) resulted in exceptionally high photocurrent reaching 14 mA/cm2 at 1.0 VSCE. This enhancement in the photocurrent is related to the synergistic effects of Ag decoration, nitrogen doping, and the unique structural properties of the fabricated nanotube arrays.